2013
DOI: 10.1061/jhtrcq.0000308
|View full text |Cite
|
Sign up to set email alerts
|

Experiment of Tension-compression Fatigue and Damage for Asphalt Mixtures

Abstract: A tension-compression beam fatigue test under continuous sine wave alternating loading for AC-13 was conducted to understand fatigue damage characteristics of an actual asphalt pavement structure under tension and compression stresses. Ten sion-compression fatigue damage characteristics of asphalt mixtures were investigated using phenomenology based on basic theory of damage mechanics. Tension-compression fatigue test method and influencing factors were introduced; and tension-compres sion fatigue equation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…The maximum axial stress and corresponding strain at the sample end increase sharply with the increase in load eccentricity. The proper experimental setup is necessary for avoiding eccentric tension [52,53]. Therefore, both TCFT and DTFT require test samples to have a firm connection to the test system.…”
Section: Axial Fatigue Testmentioning
confidence: 99%
“…The maximum axial stress and corresponding strain at the sample end increase sharply with the increase in load eccentricity. The proper experimental setup is necessary for avoiding eccentric tension [52,53]. Therefore, both TCFT and DTFT require test samples to have a firm connection to the test system.…”
Section: Axial Fatigue Testmentioning
confidence: 99%
“…Now it is widely accepted that maximum tensile stress (strain) on the top of deck pavement, maximum interface shear stress of steel deck pavement and maximum deflection of U rib, are considered as major designing parameters for steel deck pavement [8]. Also, the first designing parameter is proposed for fatigue cracks, which is major distress in the field.…”
Section: Finite Element (Fe) Model Of Local Steel Deck Pavementmentioning
confidence: 99%
“…Although composite beam is widely recommended to evaluate the fatigue performance of HMA in the steel deck pavement, there is no research on FE model of composite beam comparing with local steel deck pavement. According to different kinds of HMA materials, steel deck and load pressure, previous research [1][2]8] have shown that maximum tensile stress (strain) usually are 0.3Mpa-0.9Mpa and 300uԐ-600uԐ, respectively, which are much larger than normal asphalt pavement.…”
Section: Finite Element (Fe) Model Of Composite Beammentioning
confidence: 99%
“…The bottom of the surface layer is primarily under pressure when the vehicle wheel is close to a given point of the pavement; the bottom of the layer is under tension when vehicle crosses the given point; and then, it is under pressure once again when the vehicle leaves. By the end, the pavement structure is under tensile and compressive stresses (Qian et al, 2013). The test consists in applying a tension-compression sinusoidal loading in a cylindrical asphalt mix sample at 10Hz of frequency at different temperatures.…”
Section: Tension-compression Testmentioning
confidence: 99%